2021
DOI: 10.3390/life11030232
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondria in Viral Infections

Abstract: Viral diseases account for an increasing proportion of deaths worldwide. Viruses maneuver host cell machinery in an attempt to subvert the intracellular environment favorable for their replication. The mitochondrial network is highly susceptible to physiological and environmental insults, including viral infections. Viruses affect mitochondrial functions and impact mitochondrial metabolism, and innate immune signaling. Resurgence of host-virus interactions in recent literature emphasizes the key role of mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 136 publications
1
38
0
1
Order By: Relevance
“…In this context, SARS-CoV-2 was shown to induce vascular endothelial cell dysfunction with SARS-CoV-2 spike protein leading to ACE2 downregulation [ 36 ] and impaired mitochondrial function [ 37 ]. Moreover, mitochondrial damage might play a relevant role in COVID-19 pathogenesis, as SARS-CoV-2 interacts via mitochondrial antiviral signaling protein (MAVS), finally impairing type I interferon production and leading to reduced mitochondrial oxygen sensing, oxidative stress-associated thrombocyte dysfunction, and induction of hemostatic pathways [ 38 ]. Other than that, Rovas et al analyzed the vascular density, red blood cell velocity, and glycocalyx dimensions in tongue base microvessels via intravital microscopy by sidestream dark-field imaging in healthy individuals, nonventilated and ventilated COVID-19 patients [ 39 ], allowing for conclusions of graduated microvascular dysfunction with regard to COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, SARS-CoV-2 was shown to induce vascular endothelial cell dysfunction with SARS-CoV-2 spike protein leading to ACE2 downregulation [ 36 ] and impaired mitochondrial function [ 37 ]. Moreover, mitochondrial damage might play a relevant role in COVID-19 pathogenesis, as SARS-CoV-2 interacts via mitochondrial antiviral signaling protein (MAVS), finally impairing type I interferon production and leading to reduced mitochondrial oxygen sensing, oxidative stress-associated thrombocyte dysfunction, and induction of hemostatic pathways [ 38 ]. Other than that, Rovas et al analyzed the vascular density, red blood cell velocity, and glycocalyx dimensions in tongue base microvessels via intravital microscopy by sidestream dark-field imaging in healthy individuals, nonventilated and ventilated COVID-19 patients [ 39 ], allowing for conclusions of graduated microvascular dysfunction with regard to COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, numerous studies have revealed the association between viruses and mitochondria. During viral infections, mitochondria can be directly targeted by viral proteins (Thaker et al, 2019;Elesela and Lukacs, 2021). One theory is that virus-mitochondria interactions hamper MAVS (Refolo et al, 2020), a mitochondrial-localized anti-viral protein, leading to an inadequate host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides evidence about the mitochondrial localization of hnRNPA1. Considering the recent studies highlighting the role of mitochondria in regulating innate immune signaling in response to viral infections and the negative effect of hnRNPA1 on IAV replication characterized in this study [48,52], it can be speculated that hnRNPA1-NP co-localization in the mitochondria may be a strategy adopted by IAV to regulate mitochondrial antiviral innate immune responses to facilitate infection. However, these possibilities need to be examined in detail.…”
Section: Discussionmentioning
confidence: 80%